Atopy patch testing with aeroallergens in a large clinical population of dermatitis patients in Germany and Switzerland, 2000‐2015: a retrospective multicentre study. (9th March 2020) - Dickel, H.; Kuhlmann, L.; Bauer, A.; Bircher, A.J.; Breuer, K.; Fuchs, T.; Grabbe, J.; Mahler, V.; Pföhler, C.; Przybilla, B.; Rieker‐Schwienbacher, J.; Schröder‐Kraft, C.; et al.
Abstract: Background: The diagnostic significance of the atopy patch test for the management of dermatitis possibly triggered by aeroallergens is still controversial. However, sufficiently large studies with routinely tested standardized aeroallergen patch test preparations in dermatitis patients are lacking. Objective: To evaluate the reaction frequency and the reaction profiles of 10 until mid‐2015 commercially available, standardized aeroallergen patch test preparations of the 'Stallerpatch' test series (Stallergenes, Antony Cedex, France) in a large multicentre patient cohort. Methods: A retrospective data analysis of patients with suspected aeroallergen‐dependent eczematous skin lesions was performed, who were patch tested in 15 Information Network of Departments of Dermatology‐associated clinics between 2000 and 2015. Patients were stratified according to their atopic dermatitis (AD) status. Results: The study group included 3676 patients (median age 41 years, 34.8% males, 54.5% AD). The most common aeroallergens causing positive patch test reactions were Dermatophagoides pteronyssinus (19.6%), Dermatophagoides farinae (16.9%), birch (6.2%), timothy grass (6.0%), cat dander (5.4%), mugwort (4.9%) and dog dander (4.6%). Reactions to other pollen allergen preparations, that is 5 grasses (3.2%), cocksfoot (2.1%) and plantain (1.6%), were less common. Positive patch test reactions to aeroallergens were consistently more frequent in patients with AD. These patients showed proportionally less dubious, follicular, irritant and weak positive reactions. Independent of AD status, a patient history of past or present allergic rhinitis was associated with an increased chance of a positive aeroallergen patch test reaction to pollen allergens. Conclusion: The aeroallergen patch test is a useful add‐on tool in clinical routine, especially in patients with AD and/or respiratory allergy. A patch test series comprising Dermatophagoides pteronyssinus, Dermatophagoides farinae, birch, timothy grass, cat dander and mugwort seems to be suitable. Controlled studies with specific provocation and elimination procedures are required to further evaluate the diagnostic significance of the proposed screening series.